Effect of central sensitization on postoperative cognitive dysfunction in total knee arthroplasty patients: a retrospective study - Yang, Qiqi; Li, Chunning; Ye, Min; Zhou, Xinhua; Li, Weiran; Li, Fei (Frontiers in Neurology, 2025)
BackgroundPostoperative cognitive dysfunction (POCD) is a common complication after total knee arthroplasty (TKA), impacting recovery and quality of life. This study aims to investigate central sensitization (CS) as an independent risk factor for POCD to improve preoperative screening and postoperative interventions.MethodsA retrospective analysis was conducted on 142 TKA patients from January 2020 to May 2024 across three hospitals. Data were collected at six time points: preoperatively (T0), intraoperatively (T1), and postoperatively on days 1 (T2), 3 (T3), 7 (T4), and 30 (T5). Patients were classified into CS (CSI ≥ 40) and non-CS (CSI < 40) groups according to Central Sensitization Inventory (CSI) score. Cognitive function and POCD incidence were assessed with the Mini-Mental State Examination (MMSE), and knee recovery with the Knee Injury and Osteoarthritis Outcome Score (KOOS). Logistic regression was used to identified risk factors for POCD.ResultsThe overall incidence of POCD at T5 was 19.72%, with a significantly higher rate in CS group (30.91%) compared to non-CS group (12.64%) (p = 0.008). MMSE scores declined significantly in both groups at T2 and T3 compared to T0 (p < 0.05), with CS group showing consistently lower scores than non-CS group at T2-T5 (p < 0.05). KOOS scores revealed that CS group had worse pain and quality of life scores at T0, T4, and T5 compared with non-CS group (p < 0.05). Logistic regression revealed that CS, cerebrovascular disease, intraoperative hemorrhage, and preoperative MMSE were associated with the risk of POCD (p < 0.05).ConclusionCS is a significant risk factor for POCD following TKA, adversely affecting recovery in terms of pain and quality of life. Prospective studies are warranted to validate findings and develop targeted interventions.